A Detailed Insight onto the Molecular and Cellular Mechanism of Action of the Antifungal Drugs Used in the Treatment of Superficial Fungal Infections - Wal, Pranay; Saraswat, Nikita; Vig, Himangi (Current Drug Therapy, 2022)
Background: Dermatomycosis is a type of fungal infection that can infect human skin, hair, and nails; an increasing growth of fungal infections ranging from superficial to systemic infection is alarming. Common causative agents are Candida, Cryptococcus, Aspergillus, and Pneumocystis species. A wide range of antifungal drugs is used for the treatment of mycotic infections. These antifungal drugs can be oral or topical. The topical therapy ensures reduced side effects. Some act as fungistatic, while others act as fungicidal. These drugs work by a different mechanism of action to prevent and cure fungal infections. Objective: The effective treatment of the fungal infection includ the use of proper antifungal drug therapy. Antifungal drugs are classified into various classes. This paper focuses on understanding and interpreting the detailed molecular and cellular mechanism of action of various classes of anti-fungal drugs with their important characteristics along with the safety and efficacy data of individual drugs of the particular class. Methods: The data selection for carrying out the respective study has been made by studying the combination of review articles and research papers from different databases, like ResearchGate, PubMed, MDPI, Elsevier, ScienceDirect, and MedCrave, ranging from the year 1972 to 2019, by using the keywords like “anti-fungal agents”, “dermatophytes”, “cutaneous candidiasis”, “superficial fungal infections”, “oral candidiasis”, “amphotericin”, “echinocandins”, “azoles”, “polyenes” “ketoconazole”, “terbinafine”, “griseofulvin”, “azoles”. Result: Based on interpretation, it is concluded that the different classes of antifungal drugs follow the different mechanisms of action and target the fungal cell membrane, and are efficient in reducing fungal disease by their respective mechanism. Conclusion: The prevention and cure of fungal infections can be done by oral or topical antifungal drugs aimed to destroy the fungal cell membrane. These drugs show action by their respective pathways that are either preventing the formation of ergosterol or squalene or act by inhibiting the β-1,3- glucan synthase enzyme. All the drugs are found to be effective in treating fungal infections.
Keywords: nystatin